Knowledge management in developing regions: the case of Valle de Aburrá, Colombia. (19th July 2019) - Castro-Ramírez, Walter Darío; Gadille, Martine; Gallego-Bono, Juan Ramon; Ramírez-Carmona, Margarita
This study aims to identify the components of a knowledge management (KM) model to support innovation governance in a Colombian cosmetics cluster. The inter-organisational management of knowledge applied to innovation governance, and the perspective of endogenous economic development emphasises the structural specificities of developing countries. In line with this objective, the community-based participatory research (CBPR) and Delphi methods were combined to collect information from the cluster's different stakeholders, among them dependent shareholders who expressed their views through spokespersons. In an initial stage, a knowledge management model was built. After a second stage with a planning exercise, it integrates organisational and contextualisation proposals, together with the specificities of each of the cluster's stakeholders.